Electronic porn in the workplace: a policy examination. (1st January 2012) - Cameron, Craig
Pornography in the workplace raises issues concerning technology, law and policy. Technology has facilitated the infiltration of pornography into the workplace, policy is a tool used by employers to regulate its infiltration and the employee has a legal right to a safe workplace free of sexual harassment and discrimination. This article draws on unfair dismissal law in Australia to examine policies prohibiting electronic pornography in the workplace. A study of unfair dismissal cases reveals the dynamics of workplace pornography, the rationale for regulating pornography and the mistakes made by Australian employers when formulating and enforcing their policies. The article makes a series of recommendations which employers in any jurisdiction can use to strengthen their policies and minimise litigation risk.